`The Correlation of Sociodemographic Status, Knowledge and Attitudes with Pregnant Women's Practice Regarding COVID-19 Vaccination - Din Nurul Rasidin; Nurdin, Azizah; Trisnawaty; Jelita Inayah Sari; Muhammad Dahlan (Universitas Airlangga, 2024)
Background: Pregnant women become a high-risk group that could get infected with COVID-19 during the pandemic. Maternal mortality also has increased during the COVID-19 pandemic. Based on this, vaccination for COVID-19 becomes one of the ways to prevent the transmission of COVID-19 to pregnant women. However, there are still high doubts about the vaccine for COVID-19, especially among pregnant women. As such the authors are interested in seeing the correlation between sociodemographic status, knowledge, and attitudes with pregnant women's practice regarding COVID-19 vaccination. Aims: This study focused on evaluating the correlation of sociodemographic status, knowledge, and attitudes with pregnant women's practice regarding COVID-19 vaccination. Methods: This cross-sectional study was performed on 136 pregnant mothers determined through a purposive sampling method and implemented from February-March 2023 at Kassi-Kassi Public Health Center using a questionnaire consisting of respondent characteristics, knowledge related to COVID-19 vaccination, and attitudes toward the COVID-19 vaccination. The analysis of the data was done univariately, then bivariate using a comparative Chi-square test. Results: The correlation between variables was analyzed using the Chi-Square comparison test and significant correlation was obtained for parity (p-value; 0.000 < 0.05, OR; 1.91, CI; 1.55-2.34), age (p-value; 0.000 < 0.05, OR; 33.67, CI; 11.04-102.63), work status (p-value; 0.045 < 0.05, OR; 3.40, CI; 1.10-10.47), educational level (p-value; 0.040 < 0.05, OR; 2.77, CI; 1.14-6.72), knowledge (p-value; 0.000 < 0.05, OR; 8.45, CI; 3.64-19.61), and attitude (p-value; 0.000 < 0.05, OR; 9.20, CI; 3.88-21.78). However, there is a non-significant correlation for the monthly income category (p-value: 0.269 > 0.05, OR; 2.18, CI; 0.69-6.86). Conclusion: There is a significant correlation between sociodemographic status (parity, age, work status, and educational level), knowledge, and attitude toward pregnant women's practices regarding COVID-19 vaccination.